Islamic Perspectives on Theory Building in the Social Sciences - Ibrahim A. Ragab (International Institute of Islamic Thought, 1993)
The issue of the relevance of Islam to modem "scientific" thinking is flanked on both sides by extreme positions. On further investigation, however, these positions tun out to reflect certain misconceptions only, perpetuated by certain structural and pemnal factors that lend themselves readily to systematic analysis and, hopefully, correction. On the one hand, we have legions of Muslim social scientists who still flinch at hearing of attempts to integrate divine revelation with science. Many of them would find the title of this paper problematic, if not outright self-contradictory. What does Islam, or any other religion for that matter, have to do with science or with theory building, they would ask. This response should hardly be unexpected, considering the type of academic and professional indoctrination that we all have gone through. The scientific establishment, with its overriding positivist-empiricist leanings, has long adopted and encouraged an attitude-or more correctly a "faith"-of sepamtion between science and religion. Consider, for example, the following statement by no less an authority than the National Academy of Sciences in the United States, in 1981: Religion and science are separate and mutually exclusive realms of human thought, presentation of which in the same context leads to misunderstanding of both scientific theory and Feligious belief. (Sperry 1988, 608-9) This terse statement is representative of the attitudes of those who adhere to the old paradigm, seemingly totally oblivious of the fundamental criticisms leveled from all directions at that type of outmoded view of science. On the other hand, we have those Muslim scientists already active in the Islamic science movement who may find the content of the paper objectionable because it does not depart enough from the Western model of ...